New Trends in Sectoral Taxation - Digital Taxes - Jedlička, Vít; Jedlicka, Pavel (Univerzita Hradec Králové, 2020)
Digital economy changes not only behavior of managers and companies but also how states are governed. Expansion of digital services brings new possibilities of taxation and governments respond, otherwise they would face a drop in tax revenues. Whereas the modern economy tends to be more global, this digital tax issue is also consider by international organizations, e.g. OECD or the European Union. Both initiatives are based on international agreement how should be taxed the revenues from digital services. The size of the company is a basic assumption of digital taxation. It is important to mention that these international solutions tend to apply conditions which are more suitable for bigger countries because they have larger impact in these organizations. On the other hand, digital taxation mostly affects American companies therefore it is appropriate to discuss digital taxation with US politicians. All that confirms the experience of France which itself has applied their version of digital tax. The Czech Republic is one of the other countries which discusses the possibility of new digital tax. Overall, the tax systems have to be changed to reflect new types of services. There is no best solution but international organizations offer a suitable platform for discussions.
Nové trendy v sektorovém zdanění - digitální daně
Keywords: sectoral taxation; digital taxation; tax burden; sektorové zdanění; digitální zdanění; daňové zatížení